NMR assignment of free 1H, 15N and 13C-Grb2-SH2 domain - Sanches, Karoline [UNESP]; Caruso, Ícaro P. [UNESP]; Almeida, Fábio C. L.; Melo, Fernando A. [UNESP] (Springer Nature, 2019)
Growth factor receptor-bound protein 2 (Grb2) is an adaptor protein composed of three domains, an N-terminal SH3 (nSH3), SH2 and a C-terminal SH3 (cSH3) domains. This multi-domain protein has been reported to be a key factor in many signaling pathways related to controlling cell survival, differentiation, and growth. The Grb2-SH2 domain has been a focus for the study of the interaction with peptides and small molecules to act as inhibitors in uncontrolled cell growth, and consequently inhibit tumor proliferation. Here we describe the almost complete assignment of the free SH2 domain at pH 7. This work prepares the ground for further structural studies, backbone dynamics, mapping of interactions and drug screening and development. TalosN secondary structure prediction showed great similarity with the available structures in the PDB.
Keywords: Assignment; Grb2; Isotopic labeled; NMR; SH2 domain